Educational Leadership and Institutional Legacy of TGH. M. Yasin Abdul Lathief in Bima - Syukri Syukri; Ahmad Syagif HM (Prodi PAI STIT Sunan Giri Bima, 2025)
TGH. M. Yasin Abdul Lathief is a figure who cares deeply about education in Bima. His concern is evident in his efforts to deepen his knowledge so that he has become an intelligent, knowledgeable, and wise person. Due to his mastery of knowledge, he has been trusted since his youth to become a teacher and has served as a madrasah principal several times. His achievements were realized thanks to his persistence in pursuing knowledge and putting it into practice. This research is descriptive qualitative field research aimed at exploring the role of TGH. M. Yasin Lathief in initiating the establishment of educational institutions and developing them. The research data was obtained through interviews, observation and documentation. The results of the study show that TGH. M. Yasin Lathief made a significant contribution to the development of education in Bima. This is evidenced by his role in teaching and serving as the head of several madrasahs under the Ministry of Religious Affairs, as well as serving as the chair of the Sunan Giri Bima College of Tarbiyah (STIT) for one term. In addition, he also initiated the establishment and development of several educational institutions, including the Madrasah Ibtidaiyah Roka Belo Bima and the Darul Ma'arif Roka Belo Bima Education Foundation and Islamic Boarding School, which oversees Raudlatul Athfal (RA), Madrasah Tsanawiyah (MTs) and Madrasah Aliyah (MA) located in Roka Village, Belo District.